2019
DOI: 10.1002/adfm.201902396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Template and Molecular Nanostructure on the Performance of Organic–Inorganic Photomechanical Actuator Membranes

Abstract: Porous anodic aluminum oxide (AAO) membranes template the growth of photochromic crystalline nanowires. The resulting organic–inorganic composite can function as a photomechanical bending actuator. In order to investigate how the nanostructural properties of both the organic and inorganic components affect the photomechanical response, the composite mechanical properties are characterized using a variety of methods. There is a significant variation in both morphology and elastic modulus for two commercially av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Similar to the AAO templates, the glass templates exhibit strong light scattering, but some fraction of the incident light is transmitted to the other side, suggesting that light penetration will not limit the photochemistry. In a previous study of AAO templates, we found considerable variations in the surface pore morphology, even when comparing the top and bottom of a single template . This top–bottom asymmetry also led to an asymmetric elastic modulus for these templates, complicating any analysis of how the host mechanical properties influence the performance of the composite.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar to the AAO templates, the glass templates exhibit strong light scattering, but some fraction of the incident light is transmitted to the other side, suggesting that light penetration will not limit the photochemistry. In a previous study of AAO templates, we found considerable variations in the surface pore morphology, even when comparing the top and bottom of a single template . This top–bottom asymmetry also led to an asymmetric elastic modulus for these templates, complicating any analysis of how the host mechanical properties influence the performance of the composite.…”
Section: Resultsmentioning
confidence: 85%
“…Although the hybrid molecular crystal approach to photoactuation is promising, it also faces some difficulties. Porous AAO templates are fabricated by electrochemical etching, and we found considerable structural variability among different templates, as well as a nonuniform pore diameter across the template . They also have a limited range of pore diameters and thicknesses .…”
Section: Introductionmentioning
confidence: 90%
“…Subsequently, Bardeen et al further explored the effects that the nano-structural properties of the inorganic AAO template and organic DAE component had on the photomechanical response behavior. [257] Among the two commercially available AAO templates selected, the template with the lower average elastic modulus generated photomechanical work that was about an order of magnitude higher than the other. Adjusting the elastic modulus of the inorganic template was thus an effective way to improve the performance of the material.…”
Section: Changes In Morphologymentioning
confidence: 99%
“…35 To create macroscopic actuator structures based on this photochromism, we recently developed a bottom-up approach that assembled crystalline diarylethene nanowires inside a porous ceramic host material. 36,37 This approach was successful in generating useful mechanical motion, e.g. tilting mirrors, but variations in the template quality and filling made the production of reproducible samples a challenge.…”
Section: Introductionmentioning
confidence: 99%